60 and Counting: The History of “The Thoracic and Cardiovascular Surgeon” - Heinemann, Markus K.; Tolksdorf, Marian (The Thoracic and Cardiovascular Surgeon, 2014)
The Thoracic and Cardiovascular Surgeon was founded as a scientific journal in 1953, making it one of the oldest publications in this specialty. Bearing the original title Thoraxchirurgie, its first language of publication was German. Although the primary focus lay on thoracic surgery, the concomitantly developing specialty cardiac surgery was also well represented from the start, finally taking over the lead in submissions. After having changed its name to Thoraxchirurgie, Vaskuläre Chirurgie in 1963, it became the official journal of the German Society for Thoracic and Cardiovascular Surgery in 1973. With the language of publication having turned into English in 1979, the final title came into effect. This report gives an overview over 60 years of continued development. The history of this journal illustrates not only the transformations of the surgical disciplines reflected but also those of scientific publishing.
Keywords: cardiac; history; surgery; thoracic surgery